Short-term effect of rice straw application on soil fertility and rice yield - Md. Zulfiker Ali; Mohammad Saiful Alam; GKM Mustafizur Rahman; Md. Mizanur Rahman; Md. Moshiul Islam; Md. Ziauddin Kamal; Md. Shahadat Hossain (Eurasian Journal of Soil Science, 2021)
The study was conducted at the experimental field of the Department of Soil Science of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur, Bangladesh during July to November 2015 in transplanted aman (T. aman) season to evaluate the influence of rice straw application on growth and yield of rice (BINA dhan7) and soil fertility. The experimentation was established following a randomized complete block design (RCBD) using 3 treatments (T1= Inorganic fertilizer dose as per STB, T2= rice straw + inorganic fertilizer as IPNS basis and T3= Farmer’s practice). Results of the experiment showed that application of rice straw along with inorganic fertilizers as IPNS basis did not produce any significant (p<0.05) variation in yield and yield regulating parameters of T. aman rice but ensured higher filled grains panicle-1 (96.68), 1000- grain weight (23.23g), straw (6.97 t/ha) and grain yield (6.32 t/ha) as compared to other treatments. Short term addition of rice straw in soil did not create any significant influence on post harvest soil nutrient status except K which was found high. Significantly highest N contents in grain and straw were observed in straw added plots, which further contributed to higher nutrient uptake by grain and straw.